CULTURAL HERITAGE AND TRADITIONS OF TINNEVELLY: A COMPREHENSIVE STUDY (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive study explores the rich cultural heritage and traditions of Tinnevelly (Tirunelveli), a historically significant region in Tamil Nadu, India. By delving into the historical, religious, artistic, and social dimensions of Tinnevelly, this article highlights the diverse cultural tapestry that defines the region. The study examines the influences of various dynasties, the role of traditional festivals and rituals, the significance of classical arts and crafts, and the impact of colonial rule on the cultural landscape. Through this exploration, the article aims to provide a holistic understanding of Tinnevelly’s cultural heritage and its enduring legacy.